Loan Fund Performance Monitoring And Evaluation System Interface Based On Bkm - Eni Endaryati; Vivi Kumalasari Subroto (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
The monitoring and evaluation system is a routine process of collecting data and measuring progress on program objectives / monitoring changes, focusing on processes and outputs. The interface-based monitoring and evaluation model is one of the services provided by the operating system as a means of interaction between the user and the operating system. The interface is an operating system component that is in direct contact with the user. The research method used is Research and Development (R&D) and the application is made using Microsoft Visual Basic 6.0 and a MySQL database based on Client Server. The purpose of this system is expected to be able to process data efficiently and accurately, the second goal is to assist the financial management unit (UPK) on the input of loan installments in order to facilitate data processing so that it does not make calculation errors and records incorrectly and can improve services to self-help groups. The community (KSM) is better as a borrower, the third goal is to facilitate monitoring of the evaluation of loan funds that can be monitored and evaluated at any time, both the rate of loan repayment and the level of loan congestion.